1984
DOI: 10.1063/1.447201
|View full text |Cite
|
Sign up to set email alerts
|

Visible spectroscopy of jet-cooled SiC2: Geometry and electronic structure

Abstract: SiC2 has been prepared in a supersonic molecular beam by laser vaporization of a silicon carbide rod within a pulsed supersonic nozzle. Rotational analysis of the 0-0 band of the well-known 4980 Å band system of this molecule reveals that, contrary to previous assumptions, the molecule is triangular in both the ground and excited electronic states. In both states the molecule is of C2V symmetry with a C–Si–C angle between 40° and 41°. The correct assignment of the spectrum is Ã ′B2←x̃ ′A1. The carbon–carbon b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
88
0
2

Year Published

1992
1992
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 246 publications
(97 citation statements)
references
References 16 publications
7
88
0
2
Order By: Relevance
“…Thirty years later SiC 2 was observed in the laboratory and was shown to be the carrier of these well known optical bands [25]; however, it was mistakenly thought to be a linear molecule (i.e., Si -C -C). It was not until 1984 that an elegant two-photon ionization experiment established the ground state geometry: a three-membered ring with C 2v symmetry [26]. Approximate rotational constants derived by Michalopoulos et al [26] allowed Thaddeus et al [27] to assign nine previously unidentified lines in space to SiC 2 , to greatly improve the accuracy of the rotational constants, and to determine the leading centrifugal distortion constants.…”
Section: Sismentioning
confidence: 99%
See 1 more Smart Citation
“…Thirty years later SiC 2 was observed in the laboratory and was shown to be the carrier of these well known optical bands [25]; however, it was mistakenly thought to be a linear molecule (i.e., Si -C -C). It was not until 1984 that an elegant two-photon ionization experiment established the ground state geometry: a three-membered ring with C 2v symmetry [26]. Approximate rotational constants derived by Michalopoulos et al [26] allowed Thaddeus et al [27] to assign nine previously unidentified lines in space to SiC 2 , to greatly improve the accuracy of the rotational constants, and to determine the leading centrifugal distortion constants.…”
Section: Sismentioning
confidence: 99%
“…It was not until 1984 that an elegant two-photon ionization experiment established the ground state geometry: a three-membered ring with C 2v symmetry [26]. Approximate rotational constants derived by Michalopoulos et al [26] allowed Thaddeus et al [27] to assign nine previously unidentified lines in space to SiC 2 , to greatly improve the accuracy of the rotational constants, and to determine the leading centrifugal distortion constants. The pure rotational spectrum was measured a few years later in the laboratory by Gottlieb et al [28] who found indirect evidence for a non-rigid structure.…”
Section: Sismentioning
confidence: 99%
“…In addition CCSD(T) calculations (coupled-cluster single and double excitation model augmented with a non-iterative triple excitation correction) [27], with the 6-311G(2df) basis set, have been carried out on the B3LYP geometries. The reliability of single-referencebased methods has been tested through the socalled T 1 diagnostic [28], as well as by CASSCF (6,8) calculations (complete active space SCF calculations, including six electrons in eight orbitals) for some of the more stable CaC 3 isomers. The results were very close to those obtained with the MP2 method, thus confirming the reliability of our calculations.…”
Section: Methodsmentioning
confidence: 99%
“…Non-linear ground states have been found in many cases. For example both laboratory [6,7] and theoretical [8,9] studies have shown that SiC 2 has a cyclic ground state, whereas for SiC 3 the ground state is a rhomboidal isomer. Other theoretical works have studied the structure of aluminum, magnesium, and sodium carbides, such as AlC 2 [10][11][12][13][14][15], AlC 3 [16,17], MgC 2 [14,18,19], MgC 3 [20,21], and NaC 3 [22], concluding that several isomers are quite close in energy and might be accessible to experimental detection.…”
Section: Introductionmentioning
confidence: 99%
“…These species are then entrained in a molecular beam, from which their spectra can be studied; studies on SiC 2 are an elegant example of the power of this technique to yield rotationally resolved spectra [10]. During visits to Smalley's laboratory at Rice University, Houston, TX, USA, in 1984-1985, two thoughts occurred to Harry.…”
mentioning
confidence: 99%